2017
DOI: 10.11604/pamj.2017.27.16.9811
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs associés à la dissociation immunovirologique chez les patients infectés par le VIH-1 sous traitement antirétroviral hautement actif au Centre de Traitement Ambulatoire (CTA) de Dakar

Abstract: IntroductionL'objectif de ce travail était d'évaluer les différents facteurs associés à la dissociation immunovirologique malgré un traitement antirétroviral hautement actif et efficace.MéthodesIl s'agissait d'une étude de cohorte historique, descriptive et analytique faite à partir de dossiers de patients infectés par le VIH-1; sous traitement antirétroviral depuis au moins 12 mois, suivis dans la cohorte du CTA de 2001 à 2011 et ayant une charge virale indétectable depuis 6 mois.RésultatsDurant cette période… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…20 This implies that these participants are at risk of developing an advanced disease based on the WHO definition for advanced HIV disease. This finding, however, differs from that obtained in Benin, 68.8% 24 and in Togo 73.8%. 14 The differences may be due to the fact that these studies were done in 2004 and 2011, respectively, when the HIV/AIDS treatment initiation rates were even lower.…”
Section: Discussioncontrasting
confidence: 94%
“…20 This implies that these participants are at risk of developing an advanced disease based on the WHO definition for advanced HIV disease. This finding, however, differs from that obtained in Benin, 68.8% 24 and in Togo 73.8%. 14 The differences may be due to the fact that these studies were done in 2004 and 2011, respectively, when the HIV/AIDS treatment initiation rates were even lower.…”
Section: Discussioncontrasting
confidence: 94%
“…Previous studies have shown that the absence or cessation of ARV treatment can lead to a deterioration in clinical condition, a drop in immunity and an increase in viral load in patients who are off treatment. This contributes to an increase in morbidity and mortality related to HIV infection and to the development of resistance to antiretroviral drugs (ARVs) [6,7].…”
Section: Ofmentioning
confidence: 99%
“…However, Ka D et al in Senegal observed a male predominance of IVD (29.7%) [13]. This female predominance could be explained by the fact that women more frequently attend healthcare services and, on the other hand, constitute a vulnerable group [13].…”
Section: Discussionmentioning
confidence: 96%
“…Male gender, CD4+ T-Cell count (<200 cells/mm 3 ), Pruritus was associated with IVD. or equal to 43 years, initial CD4 count < 100 cells/mm 3 , and male gender were associated with IVD [13]. These results may be explained by the fact that some patients were initiated on ART late with a VL > 100,000 copies/mL, severe immunosuppression (CD4 < 200), which are among the factors influencing the immunovirological response in PLHIV under ART [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation